The Influence of Fashion Lifestyle and Price Through Instagram Social Media Marketing as an Intervening Variable on the Interest in Purchasing Thrifted Products - Naftalisa Metriana Sari; Djunaedi; IGG Heru Marwanto (CV. Civiliza Publishing, 2026)
Economic development and population growth have increased societal needs, particularly regarding clothing as a primary necessity. This phenomenon has sparked a thrifting trend among Generation Z, who access quality secondhand products through social media such as Instagram at affordable prices and with appealing fashion styles. This study aims to analyze the influence of fashion lifestyle and price on purchase interest, with Instagram social media marketing as an intervening variable, among Gen Z consumers of the account @nonacollectionkediri. The research employs a quantitative approach using descriptive statistical analysis and path analysis with SMART-PLS 4.0 software. Data were collected through questionnaires using a purposive sampling technique, involving 97 female respondents from Generation Z. The results indicate that purchase interest for thrifting products among Generation Z is more influenced by price factors and social media marketing strategies on Instagram, compared to fashion lifestyle. The price variable significantly affects purchase interest, both directly and indirectly through Instagram social media marketing. Conversely, fashion lifestyle is not proven to have a significant effect on purchase interest, either directly or indirectly. These findings suggest that Gen Z is more responsive to economic value and relevant digital promotion than merely to lifestyle identity.